Characterization of Ibuprofen Solid Dispersion Part-I: DTA/TG Analysis - OZLEN SAHIN, NEFISE; ARSLAN, HAKAN; ERDOGAN, CANKAT (Asian Journal of Chemistry, 2010)
In this paper, the formulation of solid dispersions of ibuprofen is suggested with skimmed milk to improve bioavailability. In order to determine the interaction between ibuprofen and skimmed milk, differential thermal analysis (DTA) and thermogravimetry (TG) studies were performed on the solid dispersion of ibuprofen as well as its individual components. Disappearance of the specific DTA peaks of the drug in DTA curve of the solid dispersion showed that the drug has interacted with the carrier. The DTA/TG curves of the solid dispersion indicated that the formation of an inclusion complex between ibuprofen and skimmed milk occurred.